Jurydic Analysis of Narcotics Circulators of Shabu Type (Decision Number: 92 / Pid.Sus / 2018 / Pn.Mdn) - Ovani Natalia Tarigan; Novriana Pandiangan; Memory Juahta Sembiring (Faculty of Law, Musamus University, 2020)
Drug abuse and dangerous drugs or drugs is a phenomenon that has long existed and experienced by all countries in the world. The circulation of narcotics among Indonesian people is also directly proportional to the development of other types of narcotics. One type of narcotics found today is a type of narcotics made with chemicals that are very dangerous for the body. One type of narcotics that is abused is methamphetamine. As Narcotics Group I, then methamphetamine has a very disturbing effect on the body's performance, namely prolonged hallucinations and dependence. Circulation involves all groups who are very troubling and worried about the nation's successors. Traders in this case means the act of offering to sell, buy, becoming an intermediary in buying and selling, exchanging, sending or receiving Narcotics Group I. Therefore, countermeasures are needed so narcotics crime can be minimized